If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 13 = -20 Reorder the terms: 13 + b = -20 Solving 13 + b = -20 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + b = -20 + -13 Combine like terms: 13 + -13 = 0 0 + b = -20 + -13 b = -20 + -13 Combine like terms: -20 + -13 = -33 b = -33 Simplifying b = -33
| 1/4(3/1) | | 12+2=2x | | 2(7-5(1-n))+2n=-12+3(6(n+1)-3n) | | -5x+1/2=-2/5x-4/5 | | ccc= | | 9x+6+60=180 | | 4-3/2n | | 2m-13=-3+27 | | 34=5(8h-6) | | -7(9x+10)=497 | | (u)+(2)+(3u)/(u+2) | | 2(7-5(1-n))+9n=-20+4(6(n+1)-3n) | | 9+7g-14+9g-17g=-6 | | -x^2=-4x+32 | | 1/4*x | | 23=-p+0 | | g-12=10 | | -10m+18=-3(5m-7)+5m | | 2(x+7)+2x=114 | | 3x-8+85=150 | | 15-1/6x=1/6x-1 | | 6x+15y+20z=1 | | 11/16+7z/8=5/16 | | -2x+2mx+b=-14 | | 2(2n+6)=5n-12-n | | -2(-5x+1)=-22 | | -10p-8q/3=7p+r/-10 | | .18m+16=4+.54m | | 26=2(2x-6)+(x+3)2 | | 3=-6c-1+2(5c-2) | | 6(5-3x)=-4(x+3) | | -1/6(x-12)+1/2(x+2)=-21 |